THU0305 Fatigue is Correlated to Pain Mechanism Rather than to Inflammatory Load in Patients with Rheumatoid Arthritis: A Descriptive Cross-Sectional Danbio Registry Survey. (9th June 2015) - Christensen, A.W.; Rifbjerg-Madsen, S.; Christensen, R.; Hetland, M.; Bliddal, H.; Kristensen, L.E.; Danneskiold-Samsø, B.; Amris, K.
Abstract : Background: In patients with rheumatoid arthritis (RA), patient reported outcomes (PROs) are sometimes reported to be refractory to therapies targeting anti-inflammatory pathways, which may be due to influence of central pain mechanisms. The painDETECT Questionnaire (PDQ), which is a validated questionnaire developed to detect neuropathic pain, assigns a score to the patient. Since its development the PDQ has also been used to link the pain phenotypic similarities of a neuropathic pain and central sensitization in osteoarthritis and fibromyalgia, and may be used as well in RA. Objectives: To examine whether fatigue is closer associated to the PDQ-score than CRP in patients with RA. Methods: An electronic version of the PDQ was added to the DANBIO touchscreens in the waiting rooms at 22 of 24 departments of Rheumatology in Denmark for a period of six months. Patient consent was obtained and corresponding data on patients diagnosed with RA in the DANBIO database were extracted. A PDQ score >18 was interpreted as an indication of predominant central pain mechanisms, 13-18 as unclear and <13 as nociceptive pain. Interactions between strata were based on Kruskal-Wallis test and correlations based on Spearman correlation coefficients. Results: Out of 15978 patients invited to participate in the survey, 9024 were diagnosed with RA. Of these, 4387 patients agreed to fill in the PDQ and 3826 patients completed it. Patients with higher PDQ-scores had higher VAS-fatigue, DAS28, VAS-global health and more tender and swollen joints (Table 1 ). VAS-fatigue correlated moderately with the PDQ-score (Rho=0.48), but not with CRP (Rho=0.09) as shown in Table 2 . Conclusions: These results suggest that fatigue, in patents with RA, shows a closer association with PDQ (indicator of clinical features of augmented central pain processing) than with CRP (indicator of inflammatory load). Disease models other than peripheral inflammatory driven models are probably needed to fully understand the mechanisms underlying individual differences in pain characteristics and might allow for a more individual approach to treatment. Acknowledgements: This study is supported financially by The Oak Foundation and Selsbjerg Holding. The authors would like to acknowledge the participating Departments of Rheumatology, DANBIO and Zitelab for their assistance. Disclosure of Interest: None declared